2006
DOI: 10.1182/blood-2005-05-2016
|View full text |Cite
|
Sign up to set email alerts
|

CD11c+ dendritic cells and plasmacytoid DCs are activated by human cytomegalovirus and retain efficient T cell-stimulatory capability upon infection

Abstract: IntroductionHuman cytomegalovirus (HCMV) infection represents a major clinical problem in immunocompromised persons, including transplant recipients and AIDS patients. Prevalence of HCMV seropositivity ranges between 50% and 90% in healthy adults; after primary infection, the virus establishes lifelong latency in the host. 1 Usually, CMV in immunocompromised patients is caused by the reactivation of latent virus. A number of studies have suggested that the virus may aggravate immunodeficiency by interfering wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
71
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 48 publications
(94 reference statements)
9
71
0
Order By: Relevance
“…Indirect immunofluorescence for IE72/86 expression, 24 h postinfection (hpi), showed that directly isolated DCs supported HCMV lytic gene expression ( Fig. 2A), consistent with a previous analysis of circulating DCs (38). Furthermore, we observed that the infection was not limited to IE protein expression, since the expression of the structural tegument protein, pp28, was clearly evident by 5 days postinfection (Fig.…”
Section: Dendritic Cells Directly Isolated From Peripheral Blood Are supporting
confidence: 72%
See 1 more Smart Citation
“…Indirect immunofluorescence for IE72/86 expression, 24 h postinfection (hpi), showed that directly isolated DCs supported HCMV lytic gene expression ( Fig. 2A), consistent with a previous analysis of circulating DCs (38). Furthermore, we observed that the infection was not limited to IE protein expression, since the expression of the structural tegument protein, pp28, was clearly evident by 5 days postinfection (Fig.…”
Section: Dendritic Cells Directly Isolated From Peripheral Blood Are supporting
confidence: 72%
“…However, crucially, while a wealth of in vitro data supports this prevailing hypothesis, it has never been definitively shown that naturally occurring DCs derived from healthy seropositive individuals are sites of genome carriage and, importantly, sites of HCMV reactivation. Indeed, a previous study of CD11c ϩ dendritic cells isolated from buffy coats of healthy volunteers has suggested that the welldocumented immunoparalysis observed following infection of in vitro-differentiated DCs (20,(30)(31)(32)(33)(34)(35)(36)(37) is not observed when circulating DCs are similarly infected in vitro with HCMV (38). Although these data concern lytic infection, they exemplify the need for a direct analysis of HCMV latency and reactivation in DCs.…”
mentioning
confidence: 90%
“…As in previous reports (15,39), these viruses infected MDCs with high efficiency and PDCs with low efficiency; only 1-12% of PDCs were IE-positive at day 1 p.i. Although late viral RNA was detected in HCMV-infected PDC cultures, the infection appeared to be mainly nonpermissive because no late viral Ags were detected.…”
Section: Discussionmentioning
confidence: 52%
“…Viral infection leads to maturation of PDCs in an autocrine manner by induced cytokine production, particularly type I IFN and TNF-␣ (27)(28)(29)(30)(31), and HCMV stimulates IFN-␣ and IL-6 secretion in PDCs after 24 -84 h of infection (39,40). We found that PDCs began secreting IFN-␣, TNF-␣, IL-6, and IL-10 within 24 h after exposure to HCMV, regardless of whether they supported viral replication.…”
Section: Discussionmentioning
confidence: 95%
“…However, even if infected DCs retain a residual capacity for Ag presentation, a series of additional viral mechanisms ranging from downregulation of costimulatory molecules over changes in the secretion of chemokines and cytokines to the inhibition of migration and maturation may severely impair DC functions (17,18,(43)(44)(45)(46)(47)(48)(49)(50)). Yet again, there are studies that report on host countermeasures that retain the function of DCs after CMV infection (51)(52)(53). Although many hints point to an important role for cross-presentation in the priming of the CMV-specific T cell response, experimental research on the contribution of cross-presentation versus direct presentation is still in an early stage.…”
mentioning
confidence: 99%